PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Arthy Suryaningtyas; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
This study aims to examine and analyze the relationship between the application of corporate governance and company value and  financial performance as a mediating variable. The dependent variable in this study is firm value (Tobin’s Q), while the independent variables are corporate governance (CGPI) and financial performance (ROE) as intervening variables. This study uses multiple regression analysis to test the research hypothesis. The test results show that the application of corporate governance has a positive effect on firm value and financial performance. This study also show that financial performance also has a positive influence on company value. In addition, this research shows that financial performance is able to mediate the relationship between corporate governance and firm value.